Power and development in practice: NGOs and the development agenda setting. Issue 3 (3rd April 2018) - Makuwira, Jonathan
ABSTRACT: There is a firm belief and evidence to suggest that local communities benefit when they are actively engaged in development processes. A parallel discourse has also gained ascendancy – one which posits that if the poor have power, they will influence institutions and processes to their advantage. NGOs have been, and continue to be, the primary proponents of this thinking. While the assertion holds some substance theoretically, in practice, there is a dearth of evidence to substantiate this claim. Using post-development and post-colonial theories, this article examines ways in which NGOs exercise and govern power in development practice.